Synthesis of Longhorn Beetle Pheromone Components by Proline-Mediated α-Hydroxylation of Alkyl Ketones - do Carmo, Hugo; Amorós, María Eugenia; González, Andrés; Heguaburu, Viviana Lucía (Synthesis, 2021)
The stereoselective synthesis of several components of the aggregation pheromones of numerous longhorn beetle species is described. These attractants consist of 3-hydroxy-2-alkanones and 2,3-alkyldiols with chain lengths varying from six to ten carbons. The 3R- and 3S-series are generated by organocatalytic α-hydroxylation of alkyl ketones with nitrosobenzene in the presence of l- or d-proline, respectively, to obtain the hydroxyketones in high enantiomeric excess. Further reduction and chromatographic separation lead to the enantiomerically pure diols that complete the library.
Keywords: (3R)-3-hydroxy-2-hexanone; (2R,3R)-2,3-hexanediol; aggregation pheromone; cerambycidae; organocatalysis